Exploring cultural differences in wildlife value orientations using student samples in seven nations - Maarten H Jacobs; Sara Dubois; Tetsuro Hosaka; Vukan Ladanović; Huda Farhana Mohamad Muslim; Kelly K. Miller; Shinya Numata; E. Ranaweerage; Tanja M. Straka; Michael A. Weston; Zulkhairi Azizi Zainal Abidin (Biodiversity and Conservation, 2022)
Understanding differences in the way people think about wildlife across countries is important as many conservation challenges transcend jurisdictions. We explored differences in wildlife value orientations in seven countries: Australia, Canada, Germany, Japan, Malaysia, the Netherlands and Serbia. Standard scales assessed domination (prioritizing human well-being) and mutualism (striving for egalitarian relationships with wildlife). We used student samples (total n = 2176) for cross-cultural comparisons. Reliabilities of the wildlife value orientations scales were adequate in all countries. Relationships between demographics and wildlife value orientations were different across countries. Men were generally more oriented towards domination and less towards mutualism than women, except in Serbia, where it was the other way around. Estimated at the level of the individual (using ANOVA), wildlife value orientations varied across countries, with nationality explaining a larger portion of the variation in mutualism (21%) than domination (6%). Estimated at the level of countries (using multilevel modelling), effect sizes were comparable. Thought about wildlife has previously only been examined within single countries. This paper makes a new contribution to the conservation literature suggesting that wildlife value orientations vary by country, and are associated with demographic factors. For conservation practices, understanding national differences in the way people think about wildlife is crucial to understanding sources of conflict among practitioners. Such knowledge is also important to gain public support for conservation.

Suitability of Wild Boar (Sus scrofa) as a Bioindicator for Environmental Pollution with Perfluorooctanoic Acid (PFOA) and Perfluorooctanesulfonic Acid (PFOS) - J. Kowalczyk; J. Numata; B. Zimmermann; R. Klinger; F. Habedank; P. Just; H. Schafft; M. Lahrssen-Wiederholt (Archives of Environmental Contamination and Toxicology, 2018)

Carbazole angular dioxygenation and mineralization by bacteria isolated from hydrocarbon-contaminated tropical African soil - L. B. Salam; M. O. Ilori; O. O. Amund; M. Numata; T. Horisaki; H. Nojiri (Environmental Science and Pollution Research, 2014)

Does the trace element composition of brown trout Salmo trutta eggs remain unchanged in spawning redds? - R. M. Gabrielsson; J. Kim; M. R. Reid; C. H. Stirling; M. Numata; G. P. Closs (Journal of Fish Biology, 2012)
The temporal stability of trace element concentrations in fertilized, artificially incubated anadromous brown trout Salmo trutta eggs and newly hatched fry was investigated. The anadromous status of the parental fish was confirmed using strontium isotopic analysis of otoliths. Whilst manganese concentrations in eggs varied over time, concentrations of aluminium, potassium, magnesium, strontium, barium and calcium were all unchanged 1 week and 6 weeks post‐fertilization as well as in recently hatched larvae. The results clearly suggest that the distinctive trace element signature present in the eggs and newly hatched larvae of anadromous S. trutta (typically characterized by high strontium, low barium) is stable over time. Therefore analysis of the trace element composition of eggs is concluded to be a cost‐effective and reliable method for determining the spatial and temporal extent of upstream spawning migration by anadromous salmonids. The temporal variability of at least one element in this study suggests the stability of untested multi‐element signatures cannot automatically be assumed.

A class V chitinase from Arabidopsis thaliana: gene responses, enzymatic properties, and crystallographic analysis - Takayuki Ohnuma; Tomoyuki Numata; Takuo Osawa; Mamiko Mizuhara; Outi Lampela; André H. Juffer; Karen Skriver; Tamo Fukamizo (Planta, 2011)

A phase response curve for circannual rhythm in the varied carpet beetle Anthrenus verbasci - Y. Miyazaki; T. Nisimura; H. Numata (Journal of Comparative Physiology A, 2005)

Association between nasal allergy and a coding variant of the Fc ε RI β gene Glu237Gly in a Japanese population - H. Nagata; H. Mutoh; K. Kumahara; Y. Arimoto; T. Tomemori; D. Sakurai; K. Arase; K. Ohno; T. Yamakoshi; K. Nakano; T. Okawa; T. Numata; et al. (Human Genetics, 2001)

The Role of Neurosecretory Neurons in the Pars Intercerebralis and Pars Lateralis in Reproductive Diapause of the Blowfly, Protophormia terraenovae - S. Shiga; H. Numata (The Science of Nature, 2000)

Neurons projecting to the retrocerebral complex of the adult blow fly, Protophormia terraenovae - S. Shiga; I. Toyoda; H. Numata (Cell and Tissue Research, 2000)

Effects of ER-34122, a novel dual 5-lipoxygenase/cyclooxygenase inhibitor, on indices of early articular lesion in MRL/MpJ-lpr/lpr mice - T. Horizoe; N. Nagakura; K. Chiba; H. Shirota; M. Shinoda; H. Numata; S. Kobayashi; C. Abe (Inflammation Research, 1999)

ER-34122, a novel dual 5-lipoxygenase/cyclooxygenase inhibitor with potent anti-inflammatory activity in an arachidonic acid-induced ear inflammation model - T. Horizoe; N. Nagakura; K. Chiba; H. Shirota; M. Shinoda; N. Kobayashi; H. Numata; Y. Okamoto; S. Kobayashi (Inflammation Research, 1998)

Induction of reproductive diapause via perception of photoperiod through the compound eyes in the adult blow fly, Protophormia terraenovae - S. Shiga; H. Numata (Journal of Comparative Physiology A, 1997)

Distribution of photoperiodic receptors in the compound eyes of the bean bug, Riptortus clavatus - A. Morita; H. Numata (Journal of Comparative Physiology A, 1997)